Industry-4.0 based teaching and learning technology: an acceptance investigation among mechanical engineering lecturers in higher TVET education institution / Mohammad Al Bukhari Marzuki and Jamal Nordin Yunus - Marzuki, Mohammad Al Bukhari; Yunus, Jamal Nordin (Universiti Teknologi MARA, Selangor, 2022)
The effect of industry 4.0 has instigated a wide range of technological development, especially in the manufacturing sector. This causes a systemic chain reaction in the education sector to prepare students for technological advancement in the industry. Higher TVET institutions play an essential role in providing highly skilled and work-ready workers to the industry due to their function in conducting work-related programs. To ensure the program is up-to-date with the current industrial revolution, the lecturers are needed to have a similar mindset and implement Industry 4.0 based courses in TVET institutions. Teaching and learning are the most crucial aspect of an educational institution. Therefore, the primary purpose of this research is to determine the level of acceptance regarding Industry 4.0 in the implementation of teaching and learning activities by utilizing the UTAUT Model. The data is collected from the lecturers of the mechanical engineering department and analyzed by utilizing the Statistical Package for Social Sciences (SPSS). Level of acceptance among mechanical engineering lecturers in a higher TVET education institution is revealed and shows a good acceptance level. The finding provides essential feedback and will inspire other researchers to explore further with a more significant sample.